Analysis Financial Performance Using the Camel Method at PT. Bank Sulselbar Period 2015-2021 - Karmila; Zainal Ruma; Nurman; Anwar Ramli; Andi Mustika Amin (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the financial performance of PT. Bank Sulselbar from 2015 to 2021 using the CAMEL method, to see if PT. Bank Sulselbar is in a healthy or unhealthy predicate. This type of research is a quantitative descriptive research. The sample used in this study is the financial statements of PT. Bank Sulselbar for the 2015-2021 period. Data collection used documentation techniques. The data analysis used is the CAMEL analysis set by Bank Indonesia. The results of this study indicate that the health level of PT. Bank Sulselbar for the 2015 to 2021 period is in the healthy predicate. This can be seen from the results of research on the CAMEL aspect for the last 7 years 2015-2021 consecutively for 2015 it was 71.62, in 2016 it was 77.28, in 2017 it was 70.66, in 2018 it was 70.90, in 2018 it was 70.90. In 2019 it was 69.70, in 2020 it was 69.53, and in 2021 it was 69.87. Based on the provisions of Bank Indonesia regarding the criteria for assessing the soundness of a bank, PT. Bank Sulselbar is in the interval 66-<81 with the Healthy Enough predicate for 2015-2021.